Ancestral agricultural knowledge in the Santa Elena Peninsula, Ecuador - Balmaseda Espinosa, Carlos Eloy (2019)
Identifying and characterizing ancestral agricultural knowledge constitutes a scientific task that facilitates the understanding of the thinking and culture of those who bequeathed us current knowledge. Validating its relevance, according to the characteristics of today, may lead to a closer approach to Agroecology, environmental protection and productive stimuli. For these reasons a project was developed in the Santa Elena Peninsula, Ecuador; the communes were visited looking for people, especially older adults, who through interviews expressed the knowledge that underlie the rural population. The objective was to contribute to the management, on a sustainable basis, of the agroecosystems of the Santa Elena Peninsula from a set of ancestral and traditional knowledge and knowledge. Nine ancestral practices were identified that should be made available to the youngest producers, examples of which are: (i) The harvest of water through the albarradas (constructions for water storage) constitutes the ancestral knowledge most recognized by all the interviewees, because the first works of this type were built by the Valdivia culture, 2000 to 1500 BC (ii) The use of rains and garúas to begin planting. (iii) Seeding of seeds, as in the case of corn is a practice that has been lost with the introduction of hybrids of various species and the modernization of planting techniques. (iv) The use of the lunar phases together with tidal fluctuations is a knowledge that is still maintained to define the timing of certain activities such as planting, harvesting and cutting wood. (v) "Shaking hands" was a cultural aspect that reflected the associativity to perform various agricultural tasks and that allowed to save resources.